Trauma Healing dan Peningkatan Resiliensi Psikososial Pasca Bencana melalui Terapi Seni dan Relaksasi pada siswa SMA Negeri 2 Umalulu - Hairunnisa, Nadjla; Rafu Lun, Eugenia; Bire Boenga, Louis; Christine Pello, Shela (Yayasan Inspirasi El Burhani, 2024)
Introduction: The Seroja disaster that hit the Umalulu area has had a significant psychological impact on students at SMA Negeri 2 Umalulu. The trauma experienced by students requires appropriate interventions to facilitate psychological recovery and increase student resilience. Objective: This community service program aims to facilitate students' psychological recovery through a trauma healing approach, with a focus on increasing psychosocial resilience, providing space for emotional expression, and reducing post-traumatic stress symptoms. Method: The activities were carried out in several sessions that included introductory sessions, art therapy, relaxation techniques, and group discussions. A total of 30 students identified as traumatized participated in the program. Evaluation was conducted before and after the intervention to measure changes in students' level of trauma and resilience. Result: The evaluation results show that students can understand the material well and feel that this activity is very useful. Students managed to express their emotions through artwork, which helped students process traumatic experiences. Conclusion: Trauma healing implemented at SMA Negeri 2 Umalulu successfully improved students' psychosocial resilience and provided necessary emotional support. Through creative and interactive approaches, students not only learn to cope with feelings of anxiety, but also find new ways to express themselves and build hope for the future.